Acceptable Postvoid Residual Urine Volume after Vaginal Delivery and Its Association with Various Obstetric Parameters. (6th August 2018) - Choe, Wen Sze; Kwang Ng, Beng; Atan, Ixora Kamisan; Lim, Pei Shan
Abstract : Background . Urinary retention and voiding dysfunction is a distressing event and relatively common in immediate postpartum period. This study aims at investigating the range of postvoid residual urine volume after vaginal delivery and its association with various obstetric parameters. Methods . This was a prospective observational study of women who delivered vaginally in Universiti Kebangsaan Malaysia Medical Centre from March 2017 to September 2017. Those who were able to void within 6 hours after delivery, the voided volume measurements were taken at their second void followed by measurement of residual urine using a transabdominal ultrasound scan. For those unable to void at 6 hours postpartum, the bladder volume was measured. If the bladder volume was 500 ml or more, an indwelling catheter would be inserted and kept for 24 hours. Results . A total of 155 patients who fulfilled the inclusion were recruited. There were 143 (92.3%) patients who had residual urine volume of less than 150 ml at second void. Out of these 143 patients, 138 (96.5%) had residual urine volume of less than 100 ml, and among the 138 patients, 119 (86.2%) had residual urine volume of less than 50 ml. The median residual urine volume was 10 ml (2, 42). The overall rate of postpartum urinary retention (PPUR) was 7.7%; 6 (3.85%) had overt retention and 6 (3.85%) had covert retention. Primiparity, duration of active phase of labour, duration of second stage of labour, epidural analgesia, episiotomy, instrumental delivery, and perineal pain score were independent risk factors associated with postpartum urinary retention. Conclusion . Postpartum urinary retention complicates approximately 7.7% of vaginal deliveries. Majority (86.2%) of them had residual urine volume less than 50 ml. Obstetrics factors independently associated with PPUR include primiparity, duration of active phase of labour, duration of second stage of labour, epidural analgesia, episiotomy, instrumental delivery, and degree of perineal pain.